Heart of a tiger - Arnold, Marsha Diane; Henterly, Jamichael (New York : Dial Books for Young Readers, 1995)
As the Name Day celebration approaches, a young kitten tries to deserve a noble name, by following the path of the beautiful Bengal tiger.
Keywords: Cats -- Fiction; Tiger -- Fiction; Names, Personal -- Fiction; India -- Fiction